Malnutrition, Sarcopenia, and Malnutrition-Sarcopenia Syndrome in Older Adults with COPD - Kaluźniak-Szymanowska, Aleksandra; Krzymińska-Siemaszko, Roma; Deskur-Śmielecka, Ewa; Lewandowicz, Marta; Kaczmarek, Beata; Wieczorowska-Tobis, Katarzyna (Nutrients, 2021)
Purpose: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death in the world population. In addition to airflow obstruction, COPD is associated with multiple systemic manifestations, including impaired nutritional status or malnutrition and changes in body composition (low muscle mass, LMM). Poor nutritional status and sarcopenia in subjects with COPD leads to a worse prognosis and increases health-related costs. Data from previous studies indicate that 30–60% of subjects with COPD are malnourished, 20–40% have low muscle mass, and 15–21.6% have sarcopenia. This study aimed to assess the prevalence of malnutrition, sarcopenia, and malnutrition-sarcopenia syndrome in elderly subjects with COPD and investigate the relationship between COPD severity and these conditions.Patients and methods: A cross-sectional study involving 124 patients with stable COPD, aged ≥60, participating in a stationary pulmonary rehabilitation program. Nutritional status was assessed following the Global Leadership Initiative on Malnutrition (GLIM) criteria and sarcopenia with the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criteria. The results of pulmonary function tests and exercise capacity were obtained from the hospital database. Results: 22.6% of participants had malnutrition according to the GLIM criteria. Subjects with malnutrition had lower gait speed (p = 0.0112) and worse results of the Six Minute Walk Test. Sixteen participants (12.9%) had sarcopenia; 12 subjects with sarcopenia had concomitant malnutrition. The prevalence of severe and very severe obstruction (GOLD3/GOLD4) was 91.7%. It was significantly higher in patients with malnutrition-sarcopenia syndrome. Conclusions: Malnutrition was found in nearly one out of four subjects with COPD, while sarcopenia was one out of seven patients. About 10% of our study sample had malnutrition-sarcopenia syndrome. The prevalence of severe and very severe obstruction was significantly higher in patients with malnutrition-sarcopenia syndrome.